A new method for network redesign via rank one updates. Issue 1 (15th March 2018) - Gernandt, Hannes; Krauße, Dominik; Sommer, Ralf; Trunk, Carsten
Abstract: We present a method to place the eigenvalues of an electrical network towards a prescribed set of complex numbers by inserting an additional capacitance into the network. For the proof, we use recent results on rank one perturbations of regular matrix pencils. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)